Aneurysmal Dermatofibroma: Uncommon Presentation of Common Disease - Patel, Shraddha; Agarwal, Pooja; Chaudhary, Raju; Baxi, Kalgi (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Aneurysmal dermatofibroma is an uncommon, benign variant of dermatofibroma due to the slow extravasation of blood. Clinically, it is difficult to differentiate from other vascular occurring lesions like verrucous hemangioma and malignancies like malignant melanoma and nodular basal cell carcinoma. Hence, an excisional biopsy followed by a thorough histopathological examination is necessary to avoid misdiagnosis. Here, we report a case of a 38 year old female who presented with a brown colored nodular lesion on her left upper back for the last one year, and histopathological examination was consistent with aneurysmal dermatofibroma.